TRADISI BERLANJUT BUDAYA AUSTRONESIA DI LIMA PULUH KOTO, SUMATERA BARAT - Rr. Triwurjani (Berkala Arkeologi, 2016)
Austronesian diaspora shows that around 60% of Austronesian-speaking people live in Indonesia. Among the locations with traces of Austronesian cultural remains is theÂ information about the diaspora of Research reveals that the continuing megalithic tradition. The problem is: if megalithic culture was brought by migrants in which Austronesian period did the menhirs should be placed, the proto-historic or recent Austronesian; how is the dispersal pattern of the menhirs; and who were the bearers of the culture. Therefore we have to reveal the form and dispersal of the megalithic culture and Austronesian migration in Lima Puluh Koto Area. The aim of this research is revealing cultural history through the migrant's adaptation within the perspective of Austronesian diaspora. Thus information about the diaspora of the Austronesians and the ethnogenesis of Indoneisan nation can be recognized. Research reveals that the continuing megalithic tradition which is used theÂ qualitative method andÂ Â assumed base on archaeological remains at Lima Puluh Koto area is a distribution of menhirs,Â that forms clusters in accordance with nagari (state) at certain area, and they are dispersed up to the hilly area. Some of these menhirs have sacred function but there are also those with profane functions like marks of village, house yard, or street boundaries, as well as the marker of village or hamlet roads.